Mechanosensitive channels of Corynebacterium glutamicum functioning as exporters of l-glutamate and other valuable metabolites. (December 2020) - Kawasaki, Hisashi; Martinac, Boris
Abstract: In the industrial l -glutamate production established on the use of Corynebacterium glutamicum, l -glutamate synthesized intracellularly is exported through mechanosensitive transmembrane channel proteins (MscCG and MscCG2) activated by the force-from-lipids. The involvement of MscCG2 in l -glutamate export by C . glutamicum was demonstrated in 2018; however, MscCG was previously found to be the major exporter of l -glutamate. Recent advances in research methods, such as development of the microbial patch clamp, revealed unique characteristics of MscCG, including its conductance, opening and closing thresholds, and gating hysteresis, as well as the significant effect of membrane lipids on the channel properties. In addition, the cryoelectron microscopic structure of Escherichia coli MscS, the canonical representative of the mechanosensitive channel family to which MscCG and MscCG2 belong, revealed its new membrane-interacting region, new position within the lipid bilayer, and hook lipids in a newly defined cavity between subunits. In this short review, the applications of bacterial mechanosensitive channels in the development of effective microbial cell factories, which will contribute to sustainable development, are discussed.